Daniel Estrada Perez and the Historical Center of Cusco: An analisis of his magement 1990-1992 - Cusicuna Vilca, Lisbeth (2021)
The municipal management of Daniel Estrada Pérez and his intervention in the public spaces of the Historic Center of Cusco, was something that no other authority had done until then; Estrada knew how to direct and use various mechanisms to insert Cusco into modernity. The objective of the article is to analyze, know and synthesize the patrimonial interventions carried out (between successes and mistakes) in the Historic Center during Estrada’s municipal administration between 1990 and 1992, this stage was considered as a starting point for the recovery of the Cusco cultural identity. To achieve the purpose of the investigation, the information gathering technique of the newspaper El Comercio de Cusco was used; At the same time, an extensive bibliographic review was carried out, contrasting sources and complements with an interview with the architect Roberto Samanez Argumedo.